PENGARUH PAJAK TANGGUHAN, KOMPENSASI MANAJEMEN DAN INTENSITAS PERSEDIAAN TERHADAP MANAJEMEN PAJAK: Studi Empiris pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang terdaftar di Bursa Efek Indonesia - Cece Piani; Mohamad Safii (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
The purpose of this research are to test the influence of Deferred Tax, Management Compensation and Inventory Intensity against Tax Management. The independent variables are used Deferred Tax, Management Compensation and Inventory Intensity. The dependent variable are used Tax Management. The study used quantitative method with secondary data. The population of this research are manufacturing company of consumer goods industry sector in Indonesia Stock Exchange 2016 - 2021. For the interpretation sample used purposive sampling method because this research have specific sample criteria agree with the purpose of this research. The study used 72 sample for manufacturing company based on purposive sampling method. The hypothesis used testing multiple regression analysis method with Eviews 12 version. The results on the F test can be known variable Deferred Tax, Management Compensation and Inventory Intensity have effect to Tax Management. The result on the T test can be known variable Deferred Tax have effect to Tax Management. The Management Compensation variable have effect to Tax Management. The Inventory Intensity have effect to Tax Management